Beyond gnosticism: myth, lifestyle, and society in the school of Valentinus - Dunderberg, Ismo (Columbia Univ. Press, 2008)
The school of Valentinus after gnosticism -- Myth, lifestyle, and the world in the fragments of Valentinus -- Immortality as a way of life -- Adam's frank speech -- Cosmic sympathy and the origin of evil -- Valentinian cosmogony, lifestyle, and other Christians -- Myth and lifestyle for beginners -- Myth and the therapy of emotions -- The Creator-God and the cosmos -- Walk like a Valentinian -- Two classes of Christians in practice -- Myth, society, and non-Christians -- Myth, society, and the oppressed church -- Myth and ethnic boundaries -- Valentinian secretiveness reconsidered -- Appendix: Remarks on the sources of Irenaeus's and Hippolytus's accounts of Valentinian theology